2020
DOI: 10.1002/term.3047
|View full text |Cite
|
Sign up to set email alerts
|

High‐fat diet selectively decreases bone marrow lin /CD117 + cell population in aging mice through increased ROS production

Abstract: Bone marrow (BM) stem cells (BMSCs) are an important source for cell therapy. The outcome of cell therapy could be ultimately associated with the number and function of donor BMSCs. The present study was to evaluate the effect of long-term high-fat diet (HFD) on the population of BMSCs and the role of reactive oxygen species (ROS) in aging mice. Forty-week-old male C57BL/6 mice were fed with HFD for 3 months with regular diet as control. Experiments were repeated when ROS production was reduced in mice treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Additionally, a previous in vivo study revealed that an HFD impairs the proliferative property of BMSCs by increasing ROS levels, which is in line with our findings. 56 Moreover, there was no change in VDR protein expression in BMSCs treated with PA + NAC (Fig. 4d, e ).…”
Section: Resultsmentioning
confidence: 87%
“…Additionally, a previous in vivo study revealed that an HFD impairs the proliferative property of BMSCs by increasing ROS levels, which is in line with our findings. 56 Moreover, there was no change in VDR protein expression in BMSCs treated with PA + NAC (Fig. 4d, e ).…”
Section: Resultsmentioning
confidence: 87%
“…This finding is in accordance with the observations documented by Xaio et al (2020) that the high cholesterol diet induced obesity in male mice resulted in increased MDA levels in obese group when compared to lean rats. The ROS act on the lipid membranes and cause excessive lipid peroxidation resulting in increased levels of MDA 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that pre-adipocytes proliferate more rapidly in fat pigs than in lean pigs [ 19 ]. In addition, several studies demonstrated that bone marrow stem cell (BMSCs) from mouse fed a high-fat diet, increased reactive oxygen species (ROS) production [ 20 ] or that obese donors lead to undesirable proliferation, differentiation, and self-renewal of BMSCs [ 21 ]. Our earlier study on undifferentiated synovial mesenchymal stem cells (SMSCs) found breed-specific transcript and signaling pathway variations related to traits like lean stature or obesity in the cell donors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%